Pengaruh Pengalaman Konsumen dan Teman Sebaya Terhadap Sikap Konsumen Menggunakan Kartu Provider Pada Mahasiswa Prodi Pendidikan Ekonomi FKIP Universitas Jambi - Kuswanto Kuswanto; Rizki Mutiara Afrilia; Iwan Putra (Universitas Negeri Surabaya, 2022)
In consuming goods and services, consumers will shape their attitudes. Based on the observations made, there is a less positive attitude formed on consumers as seen by the majority of students who have and often switch to other providers, only 21.4% of students have a positive attitude by not switching to other providers and still using the provider they use. This study aims to determine the effect of consumer experience and peers on consumer attitudes either partially or simultaneously. This research is quantitative research, with an ex post facto method. The population in this study were 140 students of the Economic Education Study Program, FKIP Universitas Jambi, batches of 2017 and 2018, and a sample of 104 people were taken by purposive sampling with the characteristics of being a provider card user. The result of this research is that consumer experience has an effect on consumer attitudes about using provider cards. Peers have an effect on consumer attitudes to using card providers. The experience of consumers and peers has a positive and significant effect on consumer attitudes in using provider cards for students of the Economic Education Study Program, FKIP Jambi University. Program, FKIP Jambi University.